Anti-toxoplasmosis activity of herbal medicines: Narrative review - Zahra Arab-Mazar; Farnaz Kheirandish*; Simin Rajaeian (Lorestan University of Medical Sciences, 2017)
Toxoplasmosis is known as a parasitic protozoan disease which is globally distributed. It is caused by Toxoplasma gondii. Sulfadiazine and pyrimethamine are two medicines utilized as parts of a standard therapy for toxoplasmosis. Since the curative medicines currently used in the treatment of toxoplasmosis bring about serious host toxicity, conducting a research on an effective and new substance characterized by relatively low toxicity is required urgently. The naturally derived herbs and plants' extracts as alternative medicines are getting increasing interest in the world.  Various studies have been conducted so far concerning the application of herbal medicines for the treatment of toxoplasmosis, but a research on relatively effective and low toxic substances is still needed. Due to increasing interest in the use of natural products to treat of infectious diseases, we conducted this study.  In this review, we have summarized the information of those herbal medicines which are reported to have anti-Toxoplasma gondii activity. We referred to the information databases of Medline, PubMed, Scopus and Google Scholar. The keywords include a combination of T.gondii and some words associated with herbal medicines and natural products.